Present day bio-invasions in the Volga-Ural Region: from the South to the North or from the East to the West? Cameraria ohridella (Lepidoptera: Gracillariidae) in the Lower and Middle Volga - Anikin, Vasiliy (Zootaxa, 2019)
The occurrence of the invasive horse-chestnut leaf miner, Cameraria ohridella, in the cities of Saratov and Samara in the Volga Region was recorded for the first time in 2018. Possible pathways of species penetration from the southern parts of European Russia are discussed.